Using Exploratory Focus Groups to Inform the Development of a Peer-Supported Pulmonary Rehabilitation Program: DIRECTIONS FOR FURTHER RESEARCH. Issue 1 (January 2017) - Poureslami, Iraj; Camp, Pat; Shum, Jessica; Afshar, Rowshanak; Tang, Tricia; FitzGerald, John Mark
Abstract : PURPOSE: There has been limited research on the role of peer support in self-management for patients with chronic obstructive pulmonary disease (COPD) attending pulmonary rehabilitation (PR) programs. This research explored patient acceptability of "peer supporters" in promoting sustained self-management practices after PR and to assess their perceived self-efficacy to manage their disease. METHODS: This qualitative study used focus groups and individual interviews to identify perspectives of peer supporters and benefits of participation in a PR program. The analysis included systematically reading and reviewing transcripts of the sessions, establishing themes, and sorting responses into thematic categories. RESULTS: A total of 28 patients with COPD (15 males) participated in either a focus group or interview. The majority of participants considered peer supporters to be good facilitators for motivating ongoing exercise after completing PR. Exercise sessions were viewed as extremely beneficial for disease management, and many were satisfied with the care they had received. Most subjects wanted to receive followup sessions with either a professional or peer after the intensive phase of PR. Overall, the concept of having a peer supporter involved in ongoing maintenance of self-management efforts after PR was generally viewed as positive. CONCLUSIONS: Integrating a peer support model into PR programs may improve better long-term health outcomes for COPD management as many participants endorsed the need for continued support after the program. It also improved our understanding of the role of "peer supports" in exercise and self-care maintenance after PR. The selection of peers and the specific model used warrants further investigation in a randomized controlled trial. Abstract : We sought to assess attitudes and perspectives of patients with chronic obstructive pulmonary disease regarding the importance and role of involving peer supporters in maintaining self-management efforts after pulmonary rehabilitation. Qualitative interviews and group sessions were conducted with 28 patients. The results revealed positive views about the concept of peer supporters in pulmonary rehabilitation.